What do we know about alcohol internet interventions aimed at employees?—A scoping review - Sundström, Christopher; Forsström, David; Berman, Anne H.; Khadjesari, Zarnie; Sundqvist, Kristina (Frontiers in Public Health, 2023)
Background Internet interventions are a promising avenue for delivering alcohol prevention to employees. The objective of this scoping review was to map all research on alcohol internet interventions aimed at employees regardless of design, to gain an overview of current evidence and identify potential knowledge gaps. Methods We conducted a literature search in three data bases (PsycInfo, PubMed, and Web of Science). Eligibility criteria were that (1) the study targeted employees age ≥18 years; (2) the intervention was delivered predominantly online; (3) the study focused specifically or in part on alcohol use; and (4) the study was published in English in a peer-reviewed academic journal. Two reviewers independently screened, reviewed, and extracted data. Results Twenty studies were included, of which 10 were randomized controlled trials, five were secondary analyses, three were feasibility trials, one was a cohort study and one described the rationale and development of an intervention. No qualitative studies were found. Randomized trials tended to show effects when interventions were compared to waitlists but not when more intensive interventions were compared to less intensive ones. We identified two design-related aspects where studies differed; (1) whether all applicants were included regardless of alcohol use level and (2) whether the intervention was explicitly framed as alcohol-focused or not. Significant recruitment problems were noted in several studies. Conclusions Alcohol internet interventions hold promise in delivering alcohol prevention to employees, but heterogeneity in study design and difficulties in recruitment complicate interpretation of findings. Systematic review registration https://osf.io/25x7e/, Open Science Framework.